India’s Relations with Muslim Countries during the Implementation of CAA/NRC: India-Indonesia and India-Malaysia Relations - Robby, Hadza Min Fadhli (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
In 2005, Imtiaz Ahmad wrote an article on the relations between India and the Muslim World. Ahmad argued that the ties between India and the Muslim World would be determined mainly by two factors: (1) the diverse and multiple identities of Indian Muslims and (2) the “relative moderation” driven by the Indian model of secularism. In the wake of the current Indian government led by the Hindu nationalist BJP, it is essential to review Ahmad’s argument. Although BJP is known as a party that strives to strengthen the Hindu nationalists’ agenda in Indian polity, it is vital to note that BJP maintains good relations with most Muslim countries. As BJP furthers its plan to scrap the special status of Kashmir and amend the Citizenship Act, there are worries that India’s stature in the Muslim World will worsen. This article would like to investigate whether the Hindu nationalist outlook in contemporary Indian politics and the standing of the current government towards Indian Muslims will eventually affect India’s relations with the Muslim World, especially in the case of India-Indonesia and India-Malaysia Relations.